2012
DOI: 10.2754/avb201281020139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fat and protein fractions of milk constituents in Montbeliarde and Polish Holstein-Friesian cows from one farm in Poland

Abstract: The aim of this study was to determine the genetic effect of cow breed on the yield and quality of cow's milk. On the selected dairy farm, cows of two different breeds Montbeliarde and Polish Holstein-Friesian between 45th -100 th days of lactation, were managed under the same environmental conditions. Milk samples were collected twice (in May and June 2008) from 97 (n = 51 and 46 for Montbeliarde and Polish Holstein-Friesian, respectively) cows. Montbeliarde cow's milk was characterized by significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
3
25
1
Order By: Relevance
“…In raw milk, some peptides were also present ( Table 1). The diff erences in protein composition between our data and data from our cited sources could be infl uenced by genetic factors and the feeding system (Barłowska et al, 2012;Brodziak at al., 2015;Król et al, 2011;Kuczyńska et al, 2012a;Kuczyńska et al, 2012b), and/or by partial hydrolysis of proteins, which was supported by the presence of peptides in the examined milk. This hydrolysis could be the result of native milk enzyme activity (plasmin) and/or proteases originating from incidental milk microfl ora (Crudden et al, 2005;Ismail and Nielsen, 2010;Yasser et al, 2010).…”
Section: Resultsmentioning
confidence: 87%
“…In raw milk, some peptides were also present ( Table 1). The diff erences in protein composition between our data and data from our cited sources could be infl uenced by genetic factors and the feeding system (Barłowska et al, 2012;Brodziak at al., 2015;Król et al, 2011;Kuczyńska et al, 2012a;Kuczyńska et al, 2012b), and/or by partial hydrolysis of proteins, which was supported by the presence of peptides in the examined milk. This hydrolysis could be the result of native milk enzyme activity (plasmin) and/or proteases originating from incidental milk microfl ora (Crudden et al, 2005;Ismail and Nielsen, 2010;Yasser et al, 2010).…”
Section: Resultsmentioning
confidence: 87%
“…The FA content has also been compared in the milk from Montbéliarde and HF cows. In the study by Kuczyńska et al (2012), the milk from Montbéliarde cows was characterized by a significantly higher level of C14:0, C18:0, 18:2cis9trans11 and total SFA, and significantly lower level of C18:2trans10cis12, C20:3n-6 and C22:6n-3 than the milk of the HF breed. Similar results were obtained in the study by Ferlay et al (2010), in which Holstein cows had lower percentages of total SFA and higher of total monounsaturated fatty acids (MUFA) and PUFA concentration, though higher percentages of CLAcis9trans11, than from Montbéliarde cows.…”
Section: Resultsmentioning
confidence: 99%
“…However, little information is available on the comparison between Holstein and Simmental cows (Barłowska et al, 2009). In addition, most breed comparison studies have been carried out under total mixed ration (TMR) systems or with grazing animals receiving supplements (Morales et al, 2000;Kliem et al, 2009;Ferlay et al, 2010;Kuczyńska et al, 2012). Only a few studies have evaluated the FA profiles and nutritional quality of milk of different breeds grazing pastures (Lawless et al, 1999;White et al, 2001;Nantapo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The average effective population size of cows of this breed was 1888 in 2011 with an average milk yield of 7 093 kg containing 3.97 % fat and 3.43 % protein (PFCB&DF 2012). Studies have shown that Montbéliarde cows in Poland have high production capacity, while their milk has a good chemical composition and high cytological quality , Januś & Borkowska 2011, Kuczyńska et al 2012. A study by Gołębiewski & Brzozowski (2009) showed that Montbéliarde heifers attained reproductive maturity considerably later than Polish Holstein-Friesian heifers.…”
Section: Introductionmentioning
confidence: 99%